Knowledge-Based Approach for Military Mission Planning and Simulation - Antkiewicz, Ryszard; Chmielewski, Mariusz; Drozdowski, Tomasz; Najgebauer, Andrzej; Rulka, Jarosław; Tarapata, Zbigniew; Wantoch-Rekowski, Roman; Pierzchała, Dariusz (IntechOpen, 2012)
None